Fractal dimension variability in ULF magnetic field with reference to local earthquakes at MPGO, Ghuttu. Issue 6 (1st November 2016) - Rawat, Gautam; Chauhan, Vishal; Dhamodharan, S.
ABSTRACT: Ultra-low frequency (ULF) geomagnetic data recorded during 1 January 2010 to 31 December 2010 at multi-parametric geophysical observatory (30.53°N, 78.74°E) in Garhwal Himalaya region of Uttarakhand, India, are analyzed. From the temporal variation of polarization ratio, the presence of seismo-magnetic disturbances superposed upon background geomagnetic variations are inferred. Considering earthquake process as a self-organized critical system based on flicker noise characteristics, fractal dimension for each day is estimated using two methods namely power spectral (FFT) method and Higuchi method. Variability in fractal dimension is studied in the background of local earthquakes ( M ≥ 3.5) within a zone of radius 150 km from observing station multi-parametric geophysical observatory (MPGO), Ghuttu. Fractal dimension variability indicates that average fractal dimension for first half of the year is increased as compared to average fractal dimension of second half of the year and there is gradual increase in the fractal dimension before earthquakes. It is also observed that during the first half of the year, there is seismic activity within zone of 150 Km radius centred at around MPGO, Ghuttu. There are no earthquakes during the second half of the year. Gradual increase in the fractal dimension before earthquakes, observed elsewhere in the world, is considered precursory signature of seismo-electromagnetic field emissions.